Placenta Previa with Succenturiate PlacentaDelivered with a Living Healthy Baby (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
The placenta is a flattened discoidal mass . Placenta with various abnormal shape like bidiscoidal, low-patiented, placenta membranacae or diffuse, placenta succenturiata, circumvallate circummarginate placentae have been less encountered but very remotely studied in relevance to clinical significance. Placenta succenturiata is a bilobbed placenta , where there is one large and one small part, connected with membranous vessels. It is associated with antepartum haemorrhage, Vasa previa, postpartum haemorrhage, retained lobe of placentae and infection. Antepartum haemorhage due to placenta succenturiata appears to be uncommonly recorded in the literature. We describe a case of placenta succenturiata , presented with antepartum haemorrhage. By LSCS a living healthy male baby of 3.3 kgs was delivered. Ultimately the Internal Iliac arteries were ligated to stop lower uterine segment bleeding.Bangladesh J Obstet Gynaecol, 2015; Vol. 30(2) : 116-118